Perceived Urban Environment Attributes and Device-Measured Physical Activity in Latin America: An 8-Nation Study - De Moraes-Ferrari, G (Elsevier Inc., 2022)
Introduction: Attributes of the neighborhood-built environment are associated with self-reported physical activity, but only a few studies have concentrated on device-measured physical activity in Latin America. This study examines the associations of perceived neighborhood-built environment attributes, device-measured sedentary time, and light-intensity and moderate-to-vigorous physical activity in adults from 8 Latin American countries. Methods: Data from Estudio Latinoamericano de Nutrición y Salud adult study, an observational multicountry study (N=2,478), were analyzed in 2020. Data were collected between 2014 and 2015. Perceived neighborhood-built environment attributes were measured using the Neighbourhood Environment Walkability Survey. Sedentary time, light-intensity physical activity, and moderate-to-vigorous physical activity data were collected using accelerometers. Results: No associations between perceived neighborhood-built environment attributes and sedentary time were found. Positive perceptions of walking/cycling facilities (β=6.50, 95% CI=2.12, 10.39) were associated with more light-intensity physical activity. Perceptions of better aesthetics (Argentina) and better walking/cycling facilities (Brazil and Ecuador) were positively associated with light-intensity physical activity. Land use mix–diversity (β=0.14, 95% CI=0.03, 0.25), walking/cycling facilities (β=0.16, 95% CI=0.05, 0.27), aesthetics (β=0.16, 95% CI=0.02, 0.30), and safety from traffic (β=0.18, 95% CI=0.05, 0.24) were positively associated with moderate-to-vigorous physical activity. Land use mix–diversity, street connectivity, and safety from traffic were positively associated with moderate-to-vigorous physical activity in Venezuela. Conclusions: These findings have implications for policy recommendations, which can guide policies to promote physical activity in the region. Land use mix–diversity, walking/cycling facilities, aesthetics, and safety from traffic can maintain or increase the levels of light-intensity and moderate-to-vigorous physical activity among Latin American adults. © 2021 American Journal of Preventive Medicine